Misthanasia: the story of a pandemic in the United Kingdom (Research, Society and Development, 2022)
A qualitative and quantitative analysis of the Sars-CoV-2 pandemic, verifying evidence of Misthanasia, even in territories with no lack of human and economic resources, due to the prioritizing of economic stabilization and the naturalization of deaths within the national public policies. As an observational territory, the United Kingdom has had its data produced and communicated in an official manner, in relation to the COVID-19 pandemic, analyzed according to analog and comparative criteria. It was possible to follow the pandemic phenomenon’s evolution through time, in virtue of regular collecting and executed under relatively standardized conditions, which allowed us to create an in-panel analytical exposition, having as a comparative model the data collected in Germany, during the same period. The origin of the data sources produced come from the Institute of Health Metrics and Evaluation (IHME); Worldometer Coronavirus. Therefore, it concludes that Misthanasia characterized the course of public policies and the attitudes of the UK’s government in sight of the Sars-CoV-2 contamination, exposing citizens to the risks of a disease that shows no class predilections and disrespects estates, and has a strong impact on those who are vulnerable. The naturalization of death configures itself on the primordial aspect of necropolitics and necropower, placing economy over health in different States, in the pandemic phenomenon of global scale.